Maternal Mortality Risk Factors and the Role of Midwives in First Handling Maternal Emergencies based on Verbal Autopsy of the 2016-2021 Maternal Perinatal Audit Program in Bandar Lampung City - Ika Fitria Elmeida; Nurlaila; Yulida Fithri (PT FORMOSA CENDEKIA GLOBAL, 2022)
The direct cause of maternal death is more than 90% due to obstetric complications, especially complications of childbirth. Complication is a complication, aggravating circumstances of a disease. Pregnancy complications are obstetric emergencies that can cause death to the mother and fetus. Pregnancy complications include hypertension and preeclampsia, anemia, and placenta previa. Meanwhile, complications of childbirth are the occurrence of difficult labor (dystosia) which causes a disease. Labor complications include premature rupture of membranes, premature labor, abnormalities in fetal position, and others (Roberts & Gammill, 2005). Knowing the risk factors for maternal death based on the main variables of delivery assistance by involving the mother's sociobiological factors, and control efforts based on verbal autopsy Maternal Perinatal Audit (AMP) in Bandar Lampung City. This study used a cross-sectional design.